Transitivity processes in the 2021 Commencement Speech of DepEd Sec. Leonor M. Briones - Simon Peter Y. Toribio; Rosette D. Morandarte; Jannet P. Paster (East Asian Journal of Multidisciplinary Research, 2023)
Grounded on Halliday's Systemic-Functional Grammar, this study explores the transitivity system in the 2021 Commencement Speech of DepEd Sec. Leonor Briones.  It specifically aims to identify the transitivity processes and the dominant process found in the Commencement speech and to analyze the linguistic functions in this transitivity system. Employing an explanatory mixed-method design, the results shows that material, mental, relational, and existential processes are present in the Commencement Speech. Among the four identified transitivity process, the dominant is the material process (65%). Moreover, it is revealed that material processes evident in the Commencement Speech display the speaker’s intention to state facts about achievements in the past and the present in response to the Covid-19 crisis that beset the Philippines, to inspire Filipino learners and teachers amidst the challenges of the pandemic, and to acknowledge the critical issue Filipino learners have been facing.